Left middle lobectomy for bronchiectasis in a patient with Kartagener syndrome: a case report. Issue 1 (December 2016) - Lin, Haiping; Cao, Ziang; Zhao, Xiaojing; Ye, Qing
Abstract Background Kartagener syndrome (KS) is a rare disorder characterized by the triad of chronic sinusitis, bronchiectasis, and situs inversus. Case presentation A 23-year-old man was admitted to our hospital because of recurrent cough with purulent expectoration, which had occurred intermittently for the past ten years. During the past 3 years, the episode frequency was 3–4 times per year. He was diagnosed with pulmonary infection and bronchiectasis of the left upper lobe, situs inversus, and KS. We concluded that the damaged left middle lobe was the source of repeat pulmonary infections. Thus the left middle lobe resection was performed to remove the source of the lung infection. Conclusions The post-operative course was successful and pneumonia was apparently resolved during the 6 months' follow-up period. We further describe this case in the following report.